(untitled) (Journal of Medical & Health Sciences Review, 2025)
Since one of the four most important qualities of nurses is caring, they should be well-versed about HIV, follow proper procedures, and have a good attitude toward patients with the virus. They should also attend to the physical, psychological, and spiritual needs of these patients because they have no prospect of recovery. The objective of this study is to assess the level of HIV-related knowledge, attitudes, and practices among nurses working in public healthcare facilities in Karachi, with a focus on their interactions with patients living with HIV. This study employed a cross-sectional descriptive approach based on a structured questionnaire. Through non-probability convenient sampling, the charge nurses employed by Karachi’s four public care institutions were chosen as the population. 100 people made up the sample. The findings showed that 37% of the nurses had great understanding of HIV, 48% had average knowledge, and the other nurses had low knowledge. The majority of responders showed a satisfactory level of practices, and the majority of nurses showed a positive attitude toward HIV patients. The overall findings showed that despite their mediocre understanding of the illness, the nurses had a compassionate demeanor and were eager to help the patients. According to the study’s findings, nurses in a few public care hospitals in the Karachi have a mediocre level of expertise, but they have a compassionate attitude toward patients who are HIV positive and are willing to help them. Nurse education and training can help to further enhance the practices and attitudes. The study’s findings call on hospital management, nursing leaders, and national health policy makers to take the appropriate steps to ensure that health care workers, particularly nurses, receive the most recent information.